The Curing Kinetics of Multiscale [Ni(EDTA)]-2 Intercalated Zn-Al Layered Double Hydroxides: Glass Fiber–Epoxy Composite Prepreg - Reza Darvishi; Mahdi Darvishi; Ali Moshkriz (International Journal of Polymer Science)
In the present research, the effect of Zn2Al layered double hydroxides (LDH) and nickel (II)-EDTA complex intercalated LDH (LDH-[Ni(EDTA)]-2) on the cure kinetics of glass fiber/epoxy prepreg (GEP) was explored using nonisothermal differential scanning calorimetry (DSC). The results showed that LDH caused a shift in the cure temperature toward lower temperatures while accelerating the curing of epoxy prepregs. The use of LDH-[Ni(EDTA)]-2 more profoundly influenced the acceleration of the curing process. The curing kinetics of prepregs was assessed through the differential isoconversional Friedman (FR) technique and the integration method of Flynn–Wall–Ozawa (FWO) and Kissinger–Akahira–Sunose (KAS). A decrease was detected in the Eα value of glass fiber/LDH-[Ni(EDTA)]-2/epoxy (GELP) and glass fiber/LDH-[Ni(EDTA)]-2/epoxy (GELNiP) prepregs at small cure degrees relative to GEP, suggesting the catalytic effect of LDH or LDH-[Ni(EDTA)]-2 on the initial epoxy/amine reaction. Furthermore, LDH-[Ni(EDTA)]-2 performed better due to the catalyst role of nickel (II). Moreover, the activation energy exhibited lower reliance on the degree of conversion in the cases of GELP and GELNiP rather than pure epoxy prepregs. An autocatalytic model was used to evaluate the curing behavior of the system. Based on the results, the curing reaction of the epoxy prepreg can be described by the autocatalytic Šesták-Berggren model even after the incorporation of LDH or LDH-[Ni(EDTA)]-2. The kinetic parameters of the autocatalytic model (such as Eα, A, m, n) and the equations explaining the curing behavior of prepregs were introduced as well whose predictions were in line with the experimental findings.